Design, development of new synthetic methodology, and biological evaluation of substituted quinolines as new anti-tubercular leads. Issue 24 (15th December 2016) - Tanwar, Babita; Kumar, Asim; Yogeeswari, Perumal; Sriram, Dharmarajan; Chakraborti, Asit K.
Graphical abstract: Abstract: Two series of quinoline-based compounds were designed, synthesised and evaluated for anti-tubercular activity against Mycobacterium tuberculosis H37 Rv (ATCC 27294 strain). A new method for Friedländer quinoline synthesis has been developed in water under the catalytic influence of the Brønsted acid surfactant DBSA. Among the forty-two compounds tested for anti-TB activity, twenty-three compounds exhibited significant activity against the growth of M. tuberculosis (MIC 0.02–6.25 μg/mL). In particular, the compounds3b and3c displayed excellent anti-TB activity with MIC values of 0.2 and 0.39 μg/mL, respectively, and are more potent than the standard drugs E, Cfx and Z that are clinically used to treat TB. The cytotoxicity of the compounds with MIC ⩽6.25 μg/mL was evaluated against Human Embryonic Kidney 293T cell lines and all of the active compounds were found to be nontoxic (<50% inhibition). The results suggest that the synthesised substituted quinolines are promising leads for development of new drug to treat TB.